Evolution and Population Structures of Prevalent Methicillin-Resistant Staphylococcus aureus in Taiwan - Chen, Chih-Jung; Yang Lauderdale, Tsai-Ling; Huang, Yhu-Chering (Frontiers in Microbiology, 2021)
Global methicillin-resistant Staphylococcus aureus (MRSA) strains were dominated by few genetic lineages suggesting their inherent advantage of competitive fitness. The information of genomes evolution and population structures of prevalent MRSA strains can help gain a better understanding of the success of the pandemic clones. Whole-genome-sequencing was performed in 340 MRSA isolates belonging to three prevalent lineages including ST59 (129 isolates), ST239/241 (140 isolates) and ST5 (71 isolates) collected from 1996 to 2016 in Taiwan. The time-scaled phylogeny and evolutionary pathways were estimated by Bayesian analysis using Markov chain Monte Carlo. The toxome, resistome and plasmids were characterized by screening the raw reads with public database. ST59, ST239/241 and ST5 MRSA were estimated to emerge in 1974, 1979 and 1995, respectively, in Taiwan. ST59 was evolved through two major pathways generating two subclones in 1980 and 1984. Both ST59 subclones remained prevalent in the healthcare and community environments in late 2010s. ST239/241was diverged into three subclones respectively in 1989, 1993 and 1995. The 1995-emerged ST239 subclone predominated after 2000 by replacing previous two early subclones. ST5 could be subdivided into two clades within three years of introduction but no substantial difference of genomic profiles was identified in the strains of distinct clades. Each of three pandemic MRSA lineages harbored its own specific toxome, resistome and plasmids. The frequently identified genetic diversities between subclones of the same lineage were genes mediating immune evasion, leukocidins, enterotoxins and resistance to aminoglycosides. In conclusion, the MRSA ST59 and ST239/241 were emerged in 1970s and evolved drastically during 1980 and 1995 resulting in three successful subclones prevailing in Taiwan. ST5 was introduced late in 1995 without significant genetic drift during 20 years of evolution.